The impact of employees' emotional intelligent on job satisfaction: the experience of employees at Vista Point Sdn Bhd - Noor Azlina S.M Fakiruddin (Management Centre, International Islamic University Malaysia, 2011)
There are many factors (such as working conditions, remuneration system, etc) that can influence employees' job satisfaction. However, major organisational behaviour literature had identified employees' emotional intelligence as a contributing factor for employees' job satisfaction. This study aims to examine the impact of employees' emotional intelligence on their job satisfaction. The research model is constructed based on the findings of previous studies. The study conducted self-administered survey to all employees at Vista Point Sdn Bhd. The results of the survey confirmed that there are positive correlations between employees' emotional intelligence and employees' job satisfaction. However, the results have to be read with a few limitations. The future research suggests bigger sample size from different companies to improve the results.